The snow spider - Nimmo, Jenny (New York : Orchard Books, 2006)
Gifts from Gwyn's grandmother on his tenth birthday open up a whole new world to him, as he discovers he has magical powers that help him heal the breach with his father that has existed ever since his sister's mysterious disappearance four years before.
Keywords: Magic -- Fiction; Fathers and sons -- Fiction; Wales -- Fiction